2009
DOI: 10.1159/000254757
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in N-Methyl-D-Aspartate Receptor Subunit NR3A but Not NR3B Influences Susceptibility to Alzheimer’s Disease

Abstract: Background: The administration of memantine, an N-methyl-D-aspartate (NMDA) receptor antagonist, has clinically improved the cognitive function of patients with Alzheimer’s disease (AD), indicating that a disturbance in glutamatergic transmission might be involved in a predisposition to developing the disease. Aim: The potential association of polymorphisms in NMDA receptor subunits NR3A and NR3B, encoded by the GRIN3A and GRIN3B genes, with AD was investigated. Methods: We performed a case-control study. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 93 publications
2
15
0
Order By: Relevance
“…In addition to changes in the NMDA receptors, the genetic variation encoding the receptors could also affect cognitive dysfunction in AD. Data from a case-control study conducted by Liu et al confirms that the exonic polymorphisms of NR3A, but not NR3B, are an important risk factor for AD pathogenesis among the Taiwanese population (Liu et al, 2009). One stereotaxic and genome-wide study confirmed that one SNP, rs10845840, which encodes the NMDA receptor NR2B subunit, is associated with temporal lobe volume and has proven to be a more informative phenotype than hippocampal volumes in AD (Stein et al, 2010).…”
Section: Alterations In Neurotransmitter Receptors In Alzheimer’s mentioning
confidence: 93%
“…In addition to changes in the NMDA receptors, the genetic variation encoding the receptors could also affect cognitive dysfunction in AD. Data from a case-control study conducted by Liu et al confirms that the exonic polymorphisms of NR3A, but not NR3B, are an important risk factor for AD pathogenesis among the Taiwanese population (Liu et al, 2009). One stereotaxic and genome-wide study confirmed that one SNP, rs10845840, which encodes the NMDA receptor NR2B subunit, is associated with temporal lobe volume and has proven to be a more informative phenotype than hippocampal volumes in AD (Stein et al, 2010).…”
Section: Alterations In Neurotransmitter Receptors In Alzheimer’s mentioning
confidence: 93%
“…Liu et al [80] studied the potential association of polymorphisms in NMDA receptor subunits NR3A and NR3B, encoded by the GRIN3A and GRIN3B genes, with AD, on the basis that memantine, an N-methyl-D-aspartate (NMDA) receptor antagonist, may provide some clinical benefit in AD patients. Two SNPs, 3104G/A (rs10989563) and 3723G/A (rs3739722), in the GRIN3A gene, and two GRIN3B gene polymorphisms, 1210C/T (rs4807399) and 1730C/T (rs2240158), were analyzed.…”
Section: Structural Genomics Of Alzheimer's Diseasementioning
confidence: 99%
“…Liu et al [75] studied the potential association of polymorphisms in NMDA receptor subunits NR3A and NR3B, encoded by the GRIN3A and GRIN3B genes, with AD, on the basis that memantine, an N-methyl-D-aspartate (NMDA) receptor antagonist, may provide some clinical benefit in AD patients. Two SNPs, 3104G/A (rs10989563) and 3723G/A (rs3739722), in the GRIN3A gene, and two GRIN3B gene polymorphisms, 1210C/T (rs4807399) and 1730C/T (rs2240158), were analyzed.…”
Section: Genomics Of Dementiamentioning
confidence: 99%